Inovasi Pelayanan Kesejahteraan Mitra UMKM Melalui Aplikasi Betang Mobile di PT. Bank Pembangunan Kalimatan Tengah - Fiqih Noverian Eka Putra; Ika Devy Pramudiana; M. Khairul Anwar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
This study aims to analyze the implementation of the Betang Mobile application as an innovation in welfare services for MSME partners at PT. Bank Pembangunan Kalimantan Tengah. The study uses a qualitative approach with in-depth interviews and document analysis to explore the experiences and perspectives of various stakeholders involved, including MSME customers, customer service, and bank management. The research method applied is a case study with an innovation diffusion theory approach as proposed by Everett M. Rogers (1995). In this study, five key characteristics of innovation diffusion relative advantage, compatibility, complexity, trialability, and observability are used to evaluate the impact and acceptance of the Betang Mobile application among MSME partners. Data collected from interviews with informants, including MSME customers and customer service, indicate that 75% of MSME players feel the application enhances service access, while 85% of users find the application compatible with their needs. The findings show that the Betang Mobile application has provided benefits in terms of efficiency and ease of access for MSME partners. About 40% of users report increased satisfaction, and 82% consider the application more efficient compared to traditional methods. Challenges include the adoption of technology by older MSME players and those in remote areas. Based on these findings, the study recommends that Bank Pembangunan Kalimantan Tengah focus on digital education for MSME partners, strengthen data security systems, and consistently update features to maintain the application's relevance. In conclusion, the Betang Mobile application has proven to make a positive contribution to the welfare services of MSME partners, with visible impacts on the accessibility and efficiency of banking services. To enhance the effectiveness of this application, it is recommended that Bank Pembangunan Kalimantan Tengah address challenges related to technology adoption and data security, as well as conduct regular evaluations of the application's features to keep them aligned with evolving user needs.